A rare case report on solitary pigmented neurofibroma over scalp region - Girishbhai, Patel Pratik; Mehta, Lav R.; Awasthi, Anuj; Talreja, Manoj; Prajapati, Chetan (International Surgery Journal, 2024)
Neurofibromas are benign proliferations that are made up of all nerve elements, and arise as fleshy and nontender, sessile or pedunculated masses on the skin. Pigmented (or melanocytic) neurofibroma constitutes only 1% of cases and is considered a rare variant of neurofibroma containing melanin-producing cells. Our patient has solitary pigmented neurofibroma over scalp region which is very rare and only few cases were reported. Here we present a case of 25 year old female patient who had brown colored swelling since birth over left temporo-parietal region which gradually increased in size with age. Patient had no any other swelling or pigmentation over any other regions of body. Patient underwent excision for the same with skin grafting. Her recovery was uneventful.